PENGGUNAAN LABORATORIUM RIIL DAN VIRTUIL PADA PEMBELAJARAN FISIKA DENGAN MODEL INKUIRI TERBIMBING DITINJAU DARI KEMAMPUAN MATEMATIS DAN KETERAMPILAN BERPIKIR KRITIS - Matsun, Matsun; Sunarno, Widha; Masykuri, M (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
This research aims at finding outÂ the differences and interaction ofÂ the implementation of teaching media, mathematical capability, and critical thinking towards the studentsâ learning achievement. The method used in this research is experimental method. The population was all IV semester students of Physics Education Department of IKIP PGRI Pontianak in the academic year of 2015/2016. The writer used cluster random sampling to get the sample. Data analysis was done by using three ways anava variansÂ analysis. Based on the data analysis, it can be concluded that: 1) there are differences of cognitive and affective learning achievement to the students who are taught by using guided inquiry model with real and virtual laboratory; 2) there are differences of studentsÂ cognitive learning achievementÂ with high and low mathematical capability; 3) there are differences to psychometric learning achievement to the students who have high and low critical thinking; 4) There is no interaction between Guided Inquiry ModelÂ using real and virual laboratory, high and low mathematical capability, andÂ high and low critical thinking towards the studentsÂ learning achievement.